On two species of Ichthyouris (Nematoda: Pharyngodonidae) parasites of Mesonauta festivus (Pisces: Cichlidae) in the Brazilian Amazon region - Melissa Q. Cárdenas; Berenice M. M. Fernandes; José Celso O. Malta; Daniel B. Porto; Aprígio M. Morais (Revista Mexicana de Biodiversidad)
Two species of nematodes belonging to the genus Ichthyouris Inglis, 1962 (I. ro and I. bursata), were collected from the cichlid fish Mesonauta festivus in the central Brazilian Amazon region. Both species are reported in this locality for the first time. I. bursata is reported in a new host, M. festivus, and this is the first report of I. ro parasitizing its type host in Brazil. We provide a more detailed description for I. ro, including morphological aspects that were not mentioned in the original description.